Skewed distribution of IL-7 receptor-α-expressing effector memory CD8+ T cells with distinct functional characteristics in oral squamous cell carcinoma. - Jang-Jaer Lee (Public Library of Science (PLoS), 2014)
CD8(+) T cells play important roles in anti-tumor immunity but distribution profile or functional characteristics of effector memory subsets during tumor progression are unclear. We found that, in oral squamous carcinoma patients, circulating CD8(+) T cell pools skewed toward effector memory subsets with the distribution frequency of CCR7(-)CD45RA(-)CD8(+) T cells and CCR7(-) CD45RA(+)CD8(+) T cells negatively correlated with each other. A significantly higher frequency of CD127(lo) CCR7(-)CD45RA(-)CD8(+) T cells or CCR7(-)CD45RA(+)CD8(+) T cells among total CD8(+) T cells was found in peripheral blood or tumor infiltrating lymphocytes, but not in regional lymph nodes. The CD127(hi) CCR7(-)CD45RA(-)CD8(+) T cells or CCR7(-)CD45RA(+)CD8(+) T cells maintained significantly higher IFN-γ, IL-2 productivity and ex vivo proliferative capacity, while the CD127(lo) CCR7(-)CD45RA(-)CD8(+) T cells or CCR7(-)CD45RA(+)CD8(+) T cells exhibited higher granzyme B productivity and susceptibility to activation induced cell death. A higher ratio of CCR7(-)CD45RA(+)CD8(+) T cells to CCR7(-)CD45RA(-)CD8(+) T cells was associated with advanced cancer staging and poor differentiation of tumor cells. Therefore, the CD127(lo) CCR7(-)CD45RA(-)CD8(+) T cells and CCR7(-)CD45RA(+)CD8(+) T cells are functionally similar CD8(+) T cell subsets which exhibit late differentiated effector phenotypes and the shift of peripheral CD8(+) effector memory balance toward CCR7(-)CD45RA(+)CD8(+) T cells is associated with OSCC progression.